Cinderella: The Feminist Tale (A Discourse Analysis of the Story’s Adaptation through Podcast) - Mardani, Puri Bestari; Christanti, Maria Febiana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Cinderella’s character and feminist ideology are contradictory. The phrase “Cinderella Complex Syndrome,” which refers to women’s dread of independence, supports this idea. Fairy tales are full of beautiful, passive, submissive princesses, as well as bold, independent female constrained by archaic gender stereotypes. They uphold conventional norms about gender roles and value. Fairy tale adaptation is not a new phenomenon; for centuries, people have used it to further their objectives, uphold their cultural standards, and further their ideologies. The construction of feminism in Cinderella rhyme via podcast is the main focus of this study. This rendition carries the feminist ideals while representing an unexpected tale. This study uses discourse analysis methodology, relying on the ideas of liberal feminism and Linda Hutcheon’s theory of adaptation. According to this theory, adaptation encompasses both the process and the final output. It is evident from Cinderella’s podcast that retelling of the narrative is dependent on the story teller’s perception and incorporates a new ideology – liberal feminism, which is associated with the second wave of feminism. This study shows how the liberal feminism ideology in Cinderella’s rhyme is constructed through modifications in the storyline and characterization. This Cinderella portrayal gives more depth that doesn’t match the image of a traditional princess and shows that she can accomplish anything she sets her mind to. This Cinderella adaptation tale shows Cinderella active role that frees herself from her oppressor as the development of liberal feminism in her character. Cinderella’s assertive voice in voicing her demands and desires also supports the liberal feminism idea.